The Internationalization Process of Tunisian Small and Medium Enterprises (SMEs) in Africa - Tamzini, Khaled (Jordan Journal of Business Administration, 2023)
In this paper, the author analyzes the role of several determinants in the internationalization process of Tunisian small and medium enterprises (SMEs) in Africa and their consequent performance. A quantitative study was carried out on 46 companies operating in information and communication technologies (ICTs). SPSS and Smart PLS were used to analyze the obtained data. The results demonstrate the importance of the total mediating role of international entrepreneurial orientation (IEO) in the relationship between competitiveness and international performance. However, networking generates a direct effect on international performance. Tunisian SMEs in the ICT industry are called upon to review their African-market methods of management and inspection to guarantee optimal use of resources and avoid the loss of business opportunities. Besides, according to this research, the weight of Tunisian SMEs’ competitive advantage allows them to adopt entrepreneurial behavior characterized by innovation, proactivity and risk-taking in Africa. This pushes them to adopt a permanent design and adaptation of valuable methods of value creation, innovation, and localization of opportunities. This entrepreneurial behavior also compels companies to better structure their management, develop skills of intuition and anticipation in the market, take risks as well as initiatives and consequently achieve greater performance and sustainability.